Pengaruh Gaji dan Insentif terhadap Kinerja Karyawan bagian produksi PT. Uniplastindo Interbuana Pandaan - Ike Ratnasari; Ashadi Mahmud (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
This study aims to describe the effect of salary and incentives on the performance of employees of PT. Unilastindo Interbuana Pandaan simultaneously, partially and most dominantly. The method used in this study is a descriptive method with a quantitative approach, data analysis techniques that are validity, reliability, multiple linear regression with F test and t test. The validity test results obtained by the calculated r value of the variable salary, incentives and employee performance is greater than the value of r proven valid tables and the reliability test results obtained a reliable value of salary, incentives and proven reliable employee performance. Based on the results of the F test (Simultaneous), known the value of sig. F count is 0.00 because the significance value of F is less than 0.05, the regression analysis model is significant. T test results explain, that the salary and incentive variables significantly influence employee performance variables, because the salary is significant 0.018 <0.05 and the incentive is significant 0.012 <0.05. The most dominant incentive variable influences employee performance, this is indicated by the value of Standardized Coefficients Beta incentive variable is greater than the salary variable. Influenced by indicators include: performance, length of work, seniority, needs, fairness and eligibility, job evaluation.